Primarna koronarna angioplastika - mehanični način odpiranja zaprtih venčnih arterij pri akutnem srčnem infarktu - Starc, Radovan (Medicinski razgledi, 1999)
This paper presents primary percutaneous transluminal coronary angioplasty used for mechanical recanalization of an infarct-related occluded coronary artery in acute myocardial infarction. Various forms of the procedure, its advantages, disadvantages, inications and contraindication are analysed in detail. When properly indicated, primary coronary angioplasty is the treatmentof choice in patients with acute myocardial infarction.
Keywords: Myocardial infarction; srčni infarkt; Therapy; srčne bolezni; Angioplasty, transluminal, percutaneous coronary; zdravljenje; Contraindications; koronarna angioplastika; Methods; Time factors